A fatal German marriage: the national subtext of Fassbinder's Die Ehe der Maria Braun - Uecker, Matthias (Wiley, 2001)
The article explores the connections between the development of Maria Braun's marriage and the political and economic conditions which made the economic miracle of the nineteen-fifties possible. Whereas Fassbinder scholarship has tended to seek parallels only between the character of Maria Braun and general developments in German society, it is argued here that both her marriage and her love affairs need to be included in such an interpretation. The analysis of non-realistic, theatrical or non-diegetic elements in the film's style discovers a subtext which revolves around symbols of national identity and sovereignty and which is directly linked to the development of Maria Braun's marriage. Within this framework, the symbolic function of Maria Braun's lovers and of her husband are re-examined.